The Understanding Basic Motor Movement Concepts for MI Mambaul Ma' Arif NU Teachers Krembun Sidoarjo - Sunanto; Pance Mariati; Muchamad Samsul Huda; Didik Purwanto (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
Based on the background above, the researchers wanted to find out how the motor skills of elementary school children after online learning during the COVID-19 pandemic. This is useful in knowing the motor skills of students after the online learning of the COVID-19 pandemic, so that the teacher can then adjust the PJOK teaching given and the appropriate method so that the motor skills of students, if previously lacking, can improve better. In addition, if students know the category of their motor skills, they can then be improved so that development and growth can be monitored properly and correctly.